(untitled) (European Bison Conservation Newsletter, 2011)
The process of formation of free-ranging population of the European bison ”Volozhynskaya” has been analyzed. Its numbers has grown from 15 to 79 in 17 years, an average annual growth is 10.7%, the home range in winter is 70 sq. km, in summer it increases to 400 sq. km and covers almost all forest area of Nalibokskaya Pushcha. The available habitat consists of flood plains overgrown with sedges in birch woods, alder and mixed spruce-deciduous forests, and especially hay meadows mainly situated along rivers: Volka, Sivichanka, Kamenka and Izled. Woody vegetation (pine, birch, buckthorn and spruce) dominates in the diet during snowy winters (over 64%). Hay, grains and root plants are used for supplemental feeding.